EDUCATIONAL AND CREATIVE MANAGEMENT TECHNOLOGY ACTIVITIES OF STUDENTS IN EXTRACURRICULAR INSTITUTIONS - Rynkova, L.V.; Rasskazova, O.I. (Pedagogy of Higher and Secondary Education, 1999)
The authors point out the main principles of management of pupils’ activities, came to the conclusion about a great meaning of mechanism of self-governing in this process. The authors present the technology of management of pupils’ studies and creative activities as the totality of stages and ways of activities corresponding to them, give examples of using rating system in the out-of-school institutions.